Parameterised approximation of the fixation probability of the dominant mutation in the multi-type Moran process - Goldberg, LA; Roth, M; Schwarz, T (Elsevier, 2024)
The multi-type Moran process is an evolutionary process on a connected graph G in which each vertex has one of k types and, in each step, a vertex v is chosen to reproduce its type to one of its neighbours. The probability of a vertex v being chosen for reproduction is proportional to the fitness of the type of v. So far, the literature was almost solely concerned with the 2-type Moran process in which each vertex is either healthy (type 0) or a mutant (type 1), and the main problem of interest has been the (approximate) computation of the so-called fixation probability, i.e., the probability that eventually all vertices are mutants. In this work we initiate the study of approximating fixation probabilities in the multi-type Moran process on general graphs. Our main result is an FPTRAS (fixed-parameter tractable randomised approximation scheme) for computing the fixation probability of the dominant mutation; the parameter is the number of types and their fitnesses. In the course of our studies we also provide novel upper bounds on the expected absorption time, i.e., the time that it takes the multi-type Moran process to reach a state in which each vertex has the same type.